Treatment with tetracycline balantidiasis - Lumbreras, Hugo (1957)
In this paper balantidiasis 4 new cases treated with tetracycline (Lederle Achromycin) with total doses ranging between 5 and 6 g are related. administered in 4 to 6 days. All patients, whose ages ranged from 17-73 years old, cured of their disease, because the discomfort disappeared and parasites as well. Parasitological and thorough checks were serially after treatment and included each time the examination of 10, 20 or 30 wet preparations with saline. The control time was between 12 and 127 days. He commented that represents the importance of antibiotic therapy in this disease, compared to that of some specific chemotherapeutic agents whose effect is not immediate and whose administration is time consuming. By contrast, the benefits of antibiotics, expressed by their specific action against Balantidium coli, its action on pathogens colonizing ulcerative lesions and, finally, its lack of toxic effects are remarked.